Adsorption Studies of Metal Cations on a Silica Static Flat Bed Using Anionic Micellar Mobile-Phase Systems Containing Carboxylic Acids: Separation of Co-Existing Iron(III), Copper(II) and Nickel(II) Cations - Ali Mohammad; Vineeta Agrawal; Sufia Hena (Adsorption Science & Technology)
Silica gel was used as a stationary phase in combination with an acidic surfactant containing eluents for the thin-layer chromatography (TLC) of 10 metal cations. Several combinations of mobile-phase systems consisting of sodium dodecyl sulphate (SDS) and carboxylic acids, alcohols and inorganic electrolytes have been tested for the rapid and reliable separation of metal cations. The TLC system employing silica gel as the stationary phase and 5% aqueous SDS plus 1% aqueous acetic acid (1:1, v/v) as the mobile phase was identified as being the most favourable system for the separation of co-existing nickel, copper and iron cations in the presence of common organic and inorganic impurities. The proposed method was rapid and applicable to the identification and separation of Fe 3+ , Cu 2+ and Ni 2+ cations from sea, river and tap water, and from real and synthetically prepared ores and alloys. The separation of microgram quantities of Cu 2+ cations from milligram quantities of Ni 2+ cations and the semi-quantitative determination of Ni 2+ cations from industrial wastewater by visual comparison were also attempted. The quantitative estimation of Fe 3+ cations by spectrophotometry after preliminary separation from Ni 2+ and Cu 2+ cations was performed successfully.